Concentrations of selected elements in permanent teeth and enamel among a group of adolescent girls in relation to severity of caries - Shahbaa M Al-Jorrani; Sulafa K El- Samarrai (College of Dentistry/ University of Baghdad, 2014)
Background: Human teeth considered to be an important etiological host factor in relation to dental caries through its morphology and composition. Elements may incorporate in tooth structure during pre and post-eruptive period changing the resistance for caries. The aims of this study were to determine the concentration of selected major (Calcium and phosphorus) and trace elements (Ferrous iron, nickel, chromium and aluminum) in permanent teeth and enamel among a group of adolescent girls in relation to severity of dental caries Material and Methods: The study group consisted of 25 girls with an age of 13-15 years old referred by Orthodontists for extractions of upper first premolars (two sides). Tooth and enamel samples were prepared for chemical analysis according to method described by Lappalainen and Knuttila (1979). Dental caries was diagnosed by both clinical and radiographical examinations following the criteria of D1-4MFS index described by Muhlemann (1976). All data were analyzed using SPSS version 19. Results: The concentration of major elements in teeth and enamel (measured in % of dry weight) showed that Ca ions were higher than P ions. On the other hand the concentration of trace elements in teeth and enamel samples (measured in ppm) showed that Al ions was the highest followed by Ferrous Fe then Ni ions, while Cr ions were the least in concentration. All elements showed statistically highly significant difference in concentration between teeth and enamel samples. Ca/P ratio was higher in enamel than tooth, but the difference was statistically not significant. Major elements (calcium and phosphorus) in tooth and enamel samples recorded negative correlations with DMFS. Trace elements except chromium ions recorded positive correlations with DMFS. They were not significant except for nickel ions in tooth and aluminum ions in enamel. Conclusions: The presence of these elements in both teeth and enamel samples indicated that these elements present in our environment; as foods, water, and air so they incorporate through out the tooth layers during the pre-eruptive period of tooth development, and incorporate the outer enamel surface during the demineralization and remineralization processes that occurs in the post-eruptive periods. Ca and p ions play an important role in mineralization of tooth and enamel. Cr ions may play a role in improving mineralization and crystallity of teeth, while Fe, Ni and Al may act as cariogenic elements.